2021
DOI: 10.1186/s13071-021-04860-w
|View full text |Cite
|
Sign up to set email alerts
|

Wild ungulate species differ in their contribution to the transmission of Ixodes ricinus-borne pathogens

Abstract: Background Several ungulate species are feeding and propagation hosts for the tick Ixodes ricinus as well as hosts to a wide range of zoonotic pathogens. Here, we focus on Anaplasma phagocytophilum and Borrelia burgdorferi (s.l.), two important pathogens for which ungulates are amplifying and dilution hosts, respectively. Ungulate management is one of the main tools to mitigate human health risks associated with these tick-borne pathogens. Across Europe, different species of ungulates are expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…This relatively high prevalence supports a primary role of roe deer in the maintenance of A. phagocytophilum in the Netherlands [ 58 ]. However, this is presumably the commonly detected non-zoonotic ecotype II [ 16 , 18 , 19 , 59 , 60 ]. Anaplasma phagocytophilum causes disease by infecting phagocytic cells, mainly neutrophils, in which it replicates and spreads to tissues [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This relatively high prevalence supports a primary role of roe deer in the maintenance of A. phagocytophilum in the Netherlands [ 58 ]. However, this is presumably the commonly detected non-zoonotic ecotype II [ 16 , 18 , 19 , 59 , 60 ]. Anaplasma phagocytophilum causes disease by infecting phagocytic cells, mainly neutrophils, in which it replicates and spreads to tissues [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified two new species for which data were lacking, fallow deer and western European hedgehog. In recent years, some papers have been published regarding some of these species, which we either included in our meta‐analysis (Coipan et al, 2018; Jahfari et al, 2017; e.g., Mysterud et al, 2015) or which did not fulfill our selection criteria (e.g., Dziemian et al, 2015; Fabri et al, 2021; Furness & Furness, 2018; Hofmeester et al, 2018; Marsot et al, 2012; Mysterud et al, 2021). In addition, our knowledge on infection prevalence of feeding I. ricinus with A. phagocytophilum is especially limited, with only data for 19 vertebrate host species (of the 77 species included in this study).…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern might be true for fallow deer that show a similar increase in distribution and population size throughout Europe (Apollonio et al, 2010), although data on tick burdens and A. phagocytophilum infection prevalence for this species are sparse. A recent study, however, found that fallow deer likely play an important role in the transmission of A. phagocytophilum (Fabri et al, 2021). Furthermore, our results suggest an important role for fluctuations in small mammal densities in determining the prevalence of mainly A. phagocytophilum Ecotype 3, but also of Ecotype 1.…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of several vertebrates in the epidemiology of Lyme borreliosis in Europe has been addressed in literally dozens of studies: not only the key role of rodents or birds as reservoirs of some species [i.e., 16 , 41 , 42 ] but also the dual role played by some taxa like large ungulates on the amplification/dilution of the pathogen [i.e., 43 , 44 ]. In the USA, research has been partly focused on the life history traits of different vertebrates, aiming to find a correlate of their contributions to the infection rates of ticks by B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%